2006
DOI: 10.1002/pola.21688
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific living radical polymerization for simultaneous control of molecular weight and tacticity

Abstract: ABSTRACT:The simultaneous control of the molecular weights and the tacticity was attained even during radical polymerization by the judicious combinations of the living/ controlled radical polymerizations based on the fast interconversion between the dormant and active species, and the stereospecific radical polymerizations mediated by the added Lewis acids or polar solvents via the coordination to the monomer/polymer terminal substituents. This can be useful for various monomers including not only conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…It has been demonstrated that certain Lewis acids of rare earth elements [in particular, lanthanide triflates like Y(OTf) 3 and Yb(OTf) 3 ] increase the content of iso structures in poly-N-isopropylamide from 44 to 66%. Fluorinated alcohols in combination with ruthenium complexes enhanced syndiotacticity of poly(methyl methacrylate) prepared at 0°С to 77% [19,51,52].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that certain Lewis acids of rare earth elements [in particular, lanthanide triflates like Y(OTf) 3 and Yb(OTf) 3 ] increase the content of iso structures in poly-N-isopropylamide from 44 to 66%. Fluorinated alcohols in combination with ruthenium complexes enhanced syndiotacticity of poly(methyl methacrylate) prepared at 0°С to 77% [19,51,52].…”
mentioning
confidence: 99%
“…This has been achieved by simultaneous addition of the Lewis acid (affecting the microstructure of the produced polymer) and the agent producing the "living" polymerization to the reaction mixture [52]. However, the Lewis acid facilitates the stereospecific growth of the polymer chain but simultaneously suppresses the effect of the second component, the product polydispersity reaching in certain cases M w /M n = 3.2.…”
mentioning
confidence: 99%
“…This material is typically synthesized by living anionic polymerization; stereospecific PMMA synthesized from controlled/ living radical polymerization has not been used previously in stereocomplexation studies. In this study, we utilized a novel syndiotactic (st-)PMMA star polymer synthesized by stereospecific living radical polymerization (SLRP) [15] and investigated its stereocomplexation behavior with linear isotactic (it-)PMMA. The macromolecular assembly of various nanoto-macroscale structures from a single pair of complementary polymers through helix formation has not been reported previously.…”
mentioning
confidence: 99%
“…38,[40][41][42] As for the metal-catalyzed living radical polymerization, we first examined the combination of the dinuclear iron(I) complex [Fe 2 Cp 2 (CO) 4 ] and lanthanide triflate (for example, Y(OTf) 3 and Yb(OTf) 3 ) to control the molecular weight and the tacticity, respectively, in the radical polymerization of acrylamide derivatives (Figure 15). 115 The low oxidation state iron(I) complex, which is one of the most active and versatile metal catalysts, induced an efficient and rather faster polymerization of N,N-dimethylacrylamide (DMAM) in the presence of Y(OTf) 3 than in its absence.…”
Section: Stereospecific Living Radical Polymerizationmentioning
confidence: 99%
“…Another further control of radical polymerization is the dual control of the polymer molecular weight and tacticity, which have not yet been fully attained. 38,[40][41][42] This review covers recent developments in metal-catalyzed living radical polymerization, focusing on our research studies, including the metal-catalytic system, the precision synthesis of well-controlled polymers, and the simultaneous control of the molecular weight and tacticity using metal-catalyzed stereospecific living radical polymerizations. Although there has been great progress in other…”
Section: Introductionmentioning
confidence: 99%